Letter - Picken, M.
1949-04-28 038-0009-001 NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF AND BASQUE CHILDREN'S TRUST LTD. PRESIDENT: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. CHAIRMAN: THE LADY LAYTON VICE-CHAIRMAN: THE EARL OF LISTOWEL. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. HON. SECRETARIES: Mr. D.R. GRENFELL, M.P. Mr. WILFRID ROBERTS, M.P. HON. APPEAL SECRETARY: Mrs. V.E. MILLER MOORE, M.B.E. SECRETARY: MISS M. PICKEN. 39, VICTORIA STREET, LONDON, S.W.1. TELEPHONE: ABBEY 7463 April 28th, 1949. Dear Mr. West, I enclose two copies of 1. An outline of the general work Mr. Volto is doing for the Spaniards 2. Individual cases. I hope you can arrange an early appointment with Mr. Tewson. Yours sincerely, M Picken 292/946/38/9(I)